Global Importance Of China Pakistan Economic Corridor (CPEC): An Analysisa - Akram, Muhammad Rehan; Mustafa, Ghulam; Liaqat, Bilal Bin (Annals of Human and Social Sciences, 2025)
The purpose of this article is to analyze the global importance of the China-Pakistan Economic Corridor (CPEC) in terms of its economic, strategic, and geopolitical impactst . CPEC, a flagship project under China’s Belt and Road Initiative, connects western China to Pakistan’s Gwadar Port, offering a strategic alternative to the Malacca Strait and reinforcing China's global trade and energy security. The research is qualitative, relying on content analysis of secondary data, including academic publications, policy reports, and case studies. CPEC enhances Pakistan’s infrastructure, energy capacity, and regional connectivity while strengthening China’s access to international markets. It also reshapes regional geopolitics, drawing responses from global actors such as India and the United States. However, it faces environmental, security, and diplomatic challenges. To mitigate these issues, CPEC must adopt green development models, strengthen regional diplomacy, and enhance internal security cooperation for successful implementation.